1974
DOI: 10.1515/znc-1974-7-807
|View full text |Cite
|
Sign up to set email alerts
|

Anthraquinones of Certain Egyptian Asphodelus Species

Abstract: The study of the anthraquinones of Asphodelus fistulosus and A. microcarpus resulted in the isolation of chrysophanol, aloe-emodin, anhydrorugulosin, three others bianthraquinones (the cleavage products of which are either 1 ,8 -dehydroxyanthraquinone or chrysophanol) and chrysophanol-8 -mono-β-ᴅ-glucoside. The obtained results revealed a qualitative difference in the anthraquinone content of the different parts (leaves, seeds and tubers).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The complete list of the identified phytoconstituents is as follows: ( 1 ) apigenin-7- O -glucosyl ( m / z 431.3), which was never reported in A. tenuifolius but reported previously from Asphodelus ramosus by Reynaud et al [ 42 ]; ( 3 ) tamgermanetin ( m / z 312.2) reported by Faidi et al [ 17 ] from A. tenuifolius ; ( 5 ) luteolin ( m / z 284.9) reported in many plants of Asphodelus genus [ 4 , 8 , 17 , 43 ]; ( 6 ) apigenin ( m / z 269.0) found in A. tenuifolius by Faidi et al and Di Petrillo et al, from Asphodelus microcarpus [ 4 , 17 ]; ( 7 ) Ramosin ( m / z 671.0) reported only one time by Adinolfi et al from A. ramosus [ 44 ]; ( 8 ) Aloe-emodin ( m / z 269.0) described by Hammouda et al from Asphodelus fistulosus and van Oudtshoorn from Asphodelus albus [ 45 , 46 ]. Recently, Khalfaoui et al [ 47 ] found both compounds ( 10 ) P ,10′ S -oxanthrone-(10′)- β -glucopyranosyl asphodelin ( m / z 668.9) and ( 12 ) M ,10′ S -oxanthrone-(10′)- β -glucopyranosyl asphodelin ( m / z 668.9) from A .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete list of the identified phytoconstituents is as follows: ( 1 ) apigenin-7- O -glucosyl ( m / z 431.3), which was never reported in A. tenuifolius but reported previously from Asphodelus ramosus by Reynaud et al [ 42 ]; ( 3 ) tamgermanetin ( m / z 312.2) reported by Faidi et al [ 17 ] from A. tenuifolius ; ( 5 ) luteolin ( m / z 284.9) reported in many plants of Asphodelus genus [ 4 , 8 , 17 , 43 ]; ( 6 ) apigenin ( m / z 269.0) found in A. tenuifolius by Faidi et al and Di Petrillo et al, from Asphodelus microcarpus [ 4 , 17 ]; ( 7 ) Ramosin ( m / z 671.0) reported only one time by Adinolfi et al from A. ramosus [ 44 ]; ( 8 ) Aloe-emodin ( m / z 269.0) described by Hammouda et al from Asphodelus fistulosus and van Oudtshoorn from Asphodelus albus [ 45 , 46 ]. Recently, Khalfaoui et al [ 47 ] found both compounds ( 10 ) P ,10′ S -oxanthrone-(10′)- β -glucopyranosyl asphodelin ( m / z 668.9) and ( 12 ) M ,10′ S -oxanthrone-(10′)- β -glucopyranosyl asphodelin ( m / z 668.9) from A .…”
Section: Resultsmentioning
confidence: 99%
“…Compounds ( 13 ) 10′ R -oxanthrone-(10′)- β -D-xylopyranoside asphodelin ( m / z 638.9), ( 14 ) 10′ S -oxanthrone-(10′)- β -D-xylopyranoside asphodelin ( m / z 639.0) and ( 15 ) 10′ S -oxanthrone-(10′)- β -L-arabinopyranoside asphodelin ( m / z 639.0) reported previously by Ghoneim et alfrom A. microcarpus [ 48 ]. Finally, ( 17 ) asphodelin ( m / z 505.0) reported in many studies from A. acaulis , A. albus , A. fistulosus and A. microcarpus [ 12 , 43 , 45 , 49 ]. However, compounds corresponding to peaks 2 , 4 , 9 , 11 and 16 are still unidentified.…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenols including trans-N-feruloyltyramine, luteolin, luteolin-7-O--D-glycopyranoside, apigenin, chrysoeriol (Khaled et al, 2014), vanillin, rutin and caffeic acid (Eddine et al, 2015) have been identified in various extracts of the plant. Anthraquoinones including chrysophanol, aloe-emodin, anhydrorugulosin; three other bianthraquinones and chrysophanol-8-mono--Dglucoside have been isolated from the plant (Basaif and Abdel-Mogib, 2002;Hammouda et al, 1974). Seeds contain considerable amount of fixed oils consisting of glycerides of myristic, palmitic, stearic, oleic and linoleic acids along with a non saponifiable component, fucosterol (Khaqn et al, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…It is even more promising by the fact that it is found in most different classes of organisms: It has been found to occur in fungi (Thomson 1997), in higher plants (Hammouda et al 1974), in lichens (Mishchenko et al 1980), and even in insects (Howard et al 1982;Hilker and Schulz 1991)-but always only in eukaryotes, never in streptomycetes or other prokaryotes.…”
Section: Introductionmentioning
confidence: 99%